2013
DOI: 10.1016/j.bmcl.2013.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of nimesulide based new class of triazole derivatives as potential PDE4B inhibitors against cancer cells

Abstract: A new class of 1,2,3-triazol derivatives derived from nimesulide was designed as potential inhibitors of PDE4B. Synthesis of these compounds was carried out via a multi-step sequence consisting of copper-catalyzed azide-alkyne cycloaddition (CuAAC) as a key step in aqueous media. The required azide was prepared via the reaction of aryl amine (obtained from nimesulide) with α-chloroacetyl chloride followed by displacing the α-chloro group by an azide. Some of the synthesized compounds showed encouraging PDE4B i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…The docking studies revealed that the interaction of PDE4B with Gln443, His234, and His278 also had potent activity towards HCT-15 human colon cancer cells. 93 1,2,3-Triazole linked nimesulide hybrids were studied against four cancer cell lines. The presence of -CH 2 O-moiety in the molecules proved to have better molecular interactions, as indicated by their activities against the cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The docking studies revealed that the interaction of PDE4B with Gln443, His234, and His278 also had potent activity towards HCT-15 human colon cancer cells. 93 1,2,3-Triazole linked nimesulide hybrids were studied against four cancer cell lines. The presence of -CH 2 O-moiety in the molecules proved to have better molecular interactions, as indicated by their activities against the cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…85 Atualmente existem duas classes de ago istas dos e epto es β : os de u ta duração como o salbutamol (28) Apesar do ressurgimento da classe ter ocorrido pela grande eficácia no tratamento da DPOC, este crescimento tem sido impulsionado também pelas diversas novas aplicações que vêm sendo estudas para estes iPDE4 com resultados bastante promissores, o que mostra um verdadeiro ressurgimento desta classe de compostos. 103 Há relatos na literatura de inibidores de PDE4 com a capacidade de inibir o crescimento de células em tumores cerebrais, de reduzir a proliferação e a angiogênese de células de linhagens de câncer de pulmão e de levar células malignas à apoptose de forma seletiva, sem afetar as células normais. 103 Mareddy e colaboradores desenvolveram compostos triazólicos derivados da nimesulida com atividade inibitória sobre a PDE4B e células de câncer de cólon da linhagem HCT-15.…”
Section: Tratamentos Disponíveis Para a Dpocunclassified
“…103 Há relatos na literatura de inibidores de PDE4 com a capacidade de inibir o crescimento de células em tumores cerebrais, de reduzir a proliferação e a angiogênese de células de linhagens de câncer de pulmão e de levar células malignas à apoptose de forma seletiva, sem afetar as células normais. 103 Mareddy e colaboradores desenvolveram compostos triazólicos derivados da nimesulida com atividade inibitória sobre a PDE4B e células de câncer de cólon da linhagem HCT-15. Um exemplo desta classe é o triazol 41 (Figura 17) que apresentou inibição de 64% da PDE4B na concentração de 30 µM.…”
Section: Tratamentos Disponíveis Para a Dpocunclassified
See 1 more Smart Citation
“…The novel nimesulide-based new class of triazole derivatives 49a–d ( Figure 24 ) were synthesized as PDE4B inhibitors [ 67 ]. The synthesized compounds were tested against cancer cells, keeping in view the reported anticancer activity of nimesulide [ 68 ] and the anti-inflammatory activity of 1,2,4-triazoles [ 69 ]. Some of the synthesized compounds exhibited significant in vitro PDE4B inhibitory properties with >50% inhibition at 30 µM.…”
Section: Selective Pde4b Inhibitorsmentioning
confidence: 99%